Economic Violence and Marital Rape in Querer (Alauda Ruiz de Azúa, 2024) - Esther Ferrer Rizo (Feminismo/s, 2025)
This article argues that the series Querer (Alauda Ruiz de Azúa, 2024) shows an innovative representation of gender-based violence in Spanish documentary fiction. This new approach is achieved by focusing the plot on two aspects that have hitherto been absent from audiovisual productions: marital rape and economic violence. The relationships between the four main characters in the series are pivotal to understanding the message addressed to the audience, which is why the qualitative content analysis focuses on the characters and the different manifestations of violence against women. The general objective of this article is to examine which elements distinguish this series from the treatment given by Spanish cinema to gender-based violence. In this regard, studies on the stereotypical representation of victims and aggressors and the classification of the main strategies of audiovisual representation of violence theorised by Zecchi have been considered. The findings substantiate that Querer introduces a novel approach and execution in addressing the interconnectedness of the various manifestations of gender-based violence and the repercussions that result for each member of the family. It also focuses, in an unprecedented way, on the difficulties of proof, the wear and tear and the uncertainty that victims face in these legal proceedings when it comes to invisible violence. The article also addresses the discursive position that the series takes on the notion of sexual consent: it criticises the neutrality that the law tends to give to this concept and defends the need to link it to the context of unequal power relations in which it is negotiated.